Determining the carbon footprint of indigenous and introduced grape varieties through Life Cycle Assessment using the island of Cyprus as a case study - Litskas, Vassilis D.; Irakleous, Theodoros; Tzortzakis, Nikos G.; Stavrinides, Menelaos (My University, 2017)
EU policies and the recent Paris agreement urge for a drastic reduction of greenhouse gas (GHG) emissions to prevent a temperature rise above 2 °C at the end of the century. Global viticulture covers more than 4.6 million hectares (ha) of land, with a major part of the acreage in the semi-arid Mediterranean part of the EU, and needs to adapt to the new policy environment. The aim of the study was to determine the product carbon footprint (PCF) of indigenous and introduced grape varieties through Life Cycle Assessment (LCA) using as a case study 90 vineyards on the Mediterranean island of Cyprus. PCF determination was based on the International Organization for Standardization (ISO) protocols for greenhouse gas emissions and Intergovernmental Panel on Climate Change (IPCC) emission factors, with a system boundary from the vineyard to the winery/market door. We took into account for the first time carbon stock changes in vineyard soil, as implemented in the Cool Farm Tool and simulated alternative fertilization/soil management strategies to reduce emissions and increase carbon sequestration. The Mediterranean table grape variety Soultanina (Thompson seedless) had the highest PCF at 0.846 kg CO2-equivalents per kg of grapes, followed by the two wine varieties, the globally popular Cabernet Sauvignon at 0.556 and the indigenous white variety Xynisteri at 0.283. Fertilizers and field energy use were the carbon hot spots for grapes. The modelled scenario for footprint mitigation showed that the PCF of all three varieties can decrease by 40–67% after applying locally produced animal manure and reducing tillage frequency. The PCF of indigenous Xynisteri can get close to zero. Validation of mitigation practices through field-research is an essential step for the compliance of viticulture with global GHG emissions mitigation targets.
Keywords: Carbon balance; Carbon sequestration; Environmental impact; Sustainability; Viticulture